Buyer Behaviour towards Fast Food with Special Reference to Chicking Restaurants - Najeemudeen, K P; Panchanatham, N (Ushus Journal of Business Management, 2021)
The Indian Fast Food Industry has witnessed high growth strides in the past years, with increasing disposable income, exposure to a number of cuisines and consumers’ willingness to experiment a mix of both western and local menu. Apart from this, busy life schedule, standardized food and less time consuming processes are also fuelling the demand from domestic consumers in the industry.ChicKing is one such fast food conglomerate, specializing on fried chicken using a special recipe, spanning over a network of more than 70 outlets world over. This paper tends to analyze the buyer behaviour towards fast food restaurants based a on a questionnaire survey administered on the customers of 3 branches of ChickingRestaurant in Malappuram district of Kerala. The evaluations were done based on the responses marked in the 105 completely filled questionnaires among the total 150 circulated. Statistical tools like Percentage Analysis and Weighted Average Score test have been used for meaningful analysis and clear presentation. This study flashes light upon some unknown factors regarding the buyer behaviour towards fast food restaurants.